2019
DOI: 10.2196/11730
|View full text |Cite
|
Sign up to set email alerts
|

Public Views on Using Mobile Phone Call Detail Records in Health Research: Qualitative Study

Abstract: BackgroundMobile phone call detail records (CDRs) are increasingly being used in health research. The location element in CDRs is used in various health geographic studies, for example, to track population movement and infectious disease transmission. Vast volumes of CDRs are held by multinational organizations, which may make them available for research under various data governance regimes. However, there is an identified lack of public engagement on using CDRs for health research to contribute to an ethical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 11 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Stronger information governance featured highly, with a need for more legal sanctions for data misuse, the option to opt out, and the provision of more information on governance and security processes. The majority felt that information about the use of anonymized mobile phone data for research should be included in the terms and conditions [11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stronger information governance featured highly, with a need for more legal sanctions for data misuse, the option to opt out, and the provision of more information on governance and security processes. The majority felt that information about the use of anonymized mobile phone data for research should be included in the terms and conditions [11].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that people are content for their anonymous CDRs to be used in research, provided that appropriate safeguards are in place. However, study participants highlighted that the terms and conditions should be clearer, as should information to phone users on data collection, sharing, and uses in research [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While they saw the value of this, they wanted to be better informed, including having the option to opt-out, and they were particularly concerned about the data being sold for profit. Their views were incorporated into articles on public views and the development of an ethically-founded framework for the use of mobile phone data for health research, as well as a detailed report for O 2 [19,20].…”
Section: Discussion Topicsmentioning
confidence: 99%